Giant-cell granuloma: 2 case reports - Abdelqader Samir; Roche Nicolas; Manfredi Laurent; Papon Jean-François; Maman Louis; Ferré François (EDP Sciences, 2018)
Introduction: Giant-cell granuloma (GCG) is a benign tumor occurring almost exclusively in the jaws. These lesions remain rare but can sometime have an aggressive behavior. In this article, we will describe and follow two cases of GCG. Observations: The first case is a referred female patient, who presents a mandibular swelling. Its clinical and radiological aspects lead us to do a biopsy, with a histological result of GCG. The second case is a patient with a terminal kidney failure, referred for a buccal swelling in the upper left jaw. The cone-beam computed tomography X-ray shows a compartmentalized lesion with blurry limits. An excisional biopsy is performed and the histological diagnosis is a GCG. Discussion: Although the first patient suffers from no systemic disease, the second one presents a terminal kidney failure resulting in a chronic hyperparathyroidism. Hyperparathyroidism can activate osteoclastic resorption and create bone lesions such as brown tumors. Conclusion: The slow and asymptomatic growth of these lesions often result in a late diagnosis. It should be kept in mind as a differential diagnosis when dealing with an osteolytic lesion of the jaws with no clear etiology, especially if hyperparathyroidism or kidney failure is associated.